Welcome to Scribd, the world's digital library. Read, publish, and share books and documents. See more ➡
Standard view
Full view
of .
×
0 of .
Results for:
P. 1
Spm Add Maths Formula List Form4

# Spm Add Maths Formula List Form4

Ratings: (0)|Views: 2,272|Likes:

### Availability:

See More
See less

12/27/2013

pdf

text

original

ONE-
Add Maths Formulae List: Form 4 (Update 18/9/08)
01
Functions
Absolute Value FunctionInverse Function
f
(
x
), if
f
(
x
)
0
f
(
x
)
f
(

x
), if
f
(

x
)
<
0
If
y
=
f
(
x
)
, then
f
1
(
y
)
=
x
Remember:Object = the value of
x
Image = the value of
y
or
f
(
x
)
f
(
x
) map onto itself means
f
(
x
) =
x
Equations
General Form
ax

2
+
bx
+
c
=
0
were
a,
an
c
are constants an
a
0.
2
x

=
b

±
b
4

ac
2
a
When the equation can not be factorized.
Forming Quadratic Equation From its Roots:
If α and
β
are the roots of a quadratic equation
α
+
β
= −
b
αβ
=
c
a
a
x
2

(
α
+
β

)

x
+

αβ
=
0
or
x
2
(
SoR
)
x
+
(
PoR
)
=
0
Nature of Roots
b
2
4
ac
>
0
two real and different roots
b
2
4
ac
= 0
two real and equal roots
b
2
4
ac
<
0
no real roots
b
2
4
ac
0
the roots are real

ONE-
Functions
General Form
f
(
x
)
=
ax
2
+

bx
+
c
where
a, b
, and
c
are constants and
a
0.*Note that the highest power of an unknown of aquadratic function is
2
.
a
>
0
minimum
(smiling face)
a
<
0
maximum
Completing the square:
f
(
x
)
=
a
(
x
+
p
)
2
+
q
(i)the value o
x
,
x
=
p
(ii)min./max. value =
q
(iii)min./max. point =
(
p
,
q
)(iv)equati

on of axis of symmetry,
x
=
p
Alternative method:
f
(
x
)
=
ax
2
+

bx
+
c
a
>
0 and
f
(
x
)
>
0
a
>
0 and
f
(
x
)
<
0
abab x
<
a
or
x
>
ba
<
x
<
b
Nature of Roots
b
2
4
ac
>
0
intersects two different pointsat
x
-axis
b
2
4
ac
=
0
touch one point at
x
-axis
b
2
4
ac
<
0
does not meet
x
-axis
04 Simultaneous
Equations
To find the intersection point
solves simultaneous equation.Remember: substitute linear equation into non- linear equation.

ONE-
05 Indices and
Logarithm
Fundamental if Indices
Zero Index,
a
0
=

1
Negative Index,
a
1
=
1
a
(
a
)
1

=
bba
1
Fractional Index
a

n
=
n
a
m
a

n
=
n
Laws of Indices
a
m
×

a
n
=
a
m
+

n
a
m
÷

a

n
=
a

m
n
(
a
m
)
n

=

a
m
×
n
(
ab
)
n
=
a
n
b
n
a
a
n
( )
n
=
b
b
n
Fundamental of Logarithm
log
a
y
=
x
a
x
=
y
log
a
a
=

1log
a
a
x
=
x
log
a
1
=
0
Law of Logarithm
log
a
mn
=
log
a
m
+

log
a
n
log
m
=
log
m

log
n
a
n
a
a
log
a
m
n
= n
log
a
m
Changing the Base
log
b
=
log
c
b
a
log
a

## Activity (40)

### Showing

AllMost RecentReviewsAll NotesLikes
Ana Syahirah liked this
Aishah Bar liked this
jrpyro liked this
angelastpmblog liked this
zulksa liked this
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->